On the performance of simulation of inter-stage turbine reheat - Pellegrini, Alvise; Nikolaidis, Theoklis; Pachidis, Vassilios; Köhler, Stephan (Elsevier, 2016)
Several authors have suggested the implementation of reheat in high By-Pass Ratio (BPR) aero engines, to improve engine performance. In contrast to military afterburning, civil aero engines would aim at reducing Specific Fuel Consumption (SFC) by introducing ‘Inter-stage Turbine Reheat’ (ITR). To maximise benefits, the second combustor should be placed at an early stage of the expansion process, e.g. between the first and second High-Pressure Turbine (HPT) stages. The aforementioned cycle design requires the accurate simulation of two or more turbine stages on the same shaft. The Design Point (DP) performance can be easily evaluated by defining a Turbine Work Split (TWS) ratio between the turbine stages. However, the performance simulation of Off-Design (OD) operating points requires the calculation of the TWS parameter for every OD step, by taking into account the thermodynamic behaviour of each turbine stage, represented by their respective maps. No analytical solution of the aforementioned problem is currently available in the public domain. This paper presents an analytical methodology by which ITR can be simulated at DP and OD. Results show excellent agreement with a commercial, closed-source performance code; discrepancies range from 0% to 3.48%, and are ascribed to the different gas models implemented in the codes.
Keywords: gas turbine; simulation; inter-turbine; inter-stage; reheat; performance modelling; aircraft engines; industrial engine